Zero‐alcohol beverages: Harm‐minimisation tool or gateway drink?. (9th August 2021) - Miller, Mia; Pettigrew, Simone; Wright, Cassandra J. C.
Abstract: Zero‐alcohol beverages, classified as products containing ≤0.5% alcohol by volume, are becoming increasingly popular. These beverages may contribute to alcohol harm reduction efforts if drinkers switch to them from regular strength beverages. However, there is currently a lack of evidence to support a substitution hypothesis, particularly as alcohol companies frequently market zero‐alcohol beverages as drinks to consume in new locations, such as in the workplace, or by previously non‐drinking groups, such as pregnant women. Additionally, zero‐alcohol beverages are currently available for sale in supermarkets by all consumers, including minors. This is problematic as there is a lack of evidence around what impact consumption of zero‐alcohol beverages in youth might have on social norms and initiation of alcohol consumption. In this commentary, we explore the existing evidence on zero‐alcohol beverages and their impact on drinking behaviours, concluding that a current paucity of knowledge makes developing evidence‐based policy a challenge. As such, substantial research efforts are required to inform policies regulating the availability and marketing of zero‐alcohol beverages in Australia.